2017
DOI: 10.3390/atmos8090159
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian-Level Urban Wind Flow Enhancement with Wind Catchers

Abstract: Dense urban areas restrict air movement, causing airflow in urban street canyons to be much lower than the flow above buildings. Boosting near-ground wind speed can enhance thermal comfort in warm climates by increasing skin convective heat transfer. We explored the potential of a wind catcher to direct atmospheric wind into urban street canyons. We arranged scaled-down models of buildings with a wind catcher prototype in a water channel to simulate flow across two-dimensional urban street canyons. Velocity pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Chew et al [12] studied pedestrian-level wind enhancement in urban street canyons with wind catchers. Water channel experiments with idealized models of street canyons revealed that a wind catcher could enhance pedestrian-level wind speed by up to 2.5 times in two-dimensional canyons.…”
Section: Effects Of Urban Morphology and Obstacles To Ventilationmentioning
confidence: 99%
“…Chew et al [12] studied pedestrian-level wind enhancement in urban street canyons with wind catchers. Water channel experiments with idealized models of street canyons revealed that a wind catcher could enhance pedestrian-level wind speed by up to 2.5 times in two-dimensional canyons.…”
Section: Effects Of Urban Morphology and Obstacles To Ventilationmentioning
confidence: 99%
“…2(b). The characteristic advection timescale, τ, is defined as H/Uref [38], where Uref is the reference freestream velocity taken at z/H = 2.5, following the recommendation in the literature [11][12][13]. For the URANS simulation and LES, the time step size was fixed at 0.01τ [18,39].…”
Section: Computational Fluid Dynamics Modelsmentioning
confidence: 99%
“…The Reynolds number, Re, is defined as HUref/ν, where H is the canyon height, Uref is a reference velocity taken 2H or higher [11][12][13], and ν is the kinematic viscosity. In full-scale built environments, buildings have H on the order of 10 1 to 10 2 m. With a reference wind speed of 2 m/s, the corresponding Re is on the order of 10 6 to 10 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been defined as a relatively narrow street space formed by successive buildings on both sides of a city street [5]. Relevant studies mainly relied on field measurements [6,7], wind tunnel experiments [8][9][10], and numerical simulations [11][12][13]. Based on previous studies, important factors that influence the flow patterns and the dispersion mechanism of pollutant can be grouped into the following categories: Inflow conditions (such as wind speed, wind direction [14][15][16], turbulence intensity [17]); Geometric conditions of building structures (such as building aspect ratio [18,19] and the street canyon aspect ratio [20,21]); Ground surface and building surface conditions (such as building surface roughness and hot or cold conditions [22][23][24][25]); The impact of turbulences caused by vehicle movement [11].…”
Section: Introductionmentioning
confidence: 99%